2015
DOI: 10.1016/j.sbspro.2015.01.1171
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Loyalty is All about Prices, Culture and the Sun: A Multinomial Logistic Regression of Tourists Visiting Athens

Abstract: The objective of the paper is to identify the predictive factors of a tourist's loyalty to the tourist destination of the capital of Greece, Athens. A sample survey was carried out among the members of a random sample of 461 tourists to Athens. The questionnaire included sections about satisfaction from Athens, Image of Athens, Image of Greece, Loyalty to Athens as a destination, Word of Mouth for travelling to Athens, Demographics and questions about intention for repeat tourist visits to Athens. The methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
0
17
0
2
Order By: Relevance
“…For a long time, the quality and satisfaction of products or services have been regarded as the keys for businesses to create positive purchase intentions in their clients [39,46,47]. The prime aim of Frangos et al [48] was to determine the predictors of the possibility of sustainable operation for tourists visiting destinations in Athens, the capital of Greece. Their study used multinomial logistic regression of tourist visits to explore the factors affecting Athenian visitors, and discover the problems of potential visitors.…”
Section: Current Researchmentioning
confidence: 99%
“…For a long time, the quality and satisfaction of products or services have been regarded as the keys for businesses to create positive purchase intentions in their clients [39,46,47]. The prime aim of Frangos et al [48] was to determine the predictors of the possibility of sustainable operation for tourists visiting destinations in Athens, the capital of Greece. Their study used multinomial logistic regression of tourist visits to explore the factors affecting Athenian visitors, and discover the problems of potential visitors.…”
Section: Current Researchmentioning
confidence: 99%
“…For instance, a recent study by Frangos et al (2015) showed that repeat visitors to Athens (Greece) care more about the price of the trip and the sunny natural environment of Athens and Greece generally. For example, destinations could try to build loyalty relationships with their visitors by stimulating them to come back frequently (e.g., each year).…”
Section: Resultsmentioning
confidence: 99%
“…Municipal services and behaviour of local people, history, nature and cuisine and prices are the three categories of indicators [32]. Religious-visit the places which are important due to its religious values either for leisure or for religious needs can be implied as religious-based visits [33].…”
Section: Cultural Attractiveness: Enjoying and Examining Cultural Hermentioning
confidence: 99%